Comparison of 3Â mm versus 4Â mm rigid endoscope in diagnostic nasal endoscopy - Gregory S. Neel (KeAi Communications Co., Ltd., 2017)
Objective: Compare nasal endoscopy with 3Â mm versus conventional 4Â mm rigid 30Â° endoscopes for visualization, patient comfort, and examiner ease. Methods: Ten adults with no previous sinus surgery underwent bilateral nasal endoscopy with both 4Â mm and 3Â mm endoscopes (resulting in 20 paired nasal endoscopies). Visualization, patient discomfort and examiner's difficulty were assessed with every endoscopy. Sino-nasal structures were checked on a list if visualized satisfactorily. Patients rated discomfort on a standardized numerical pain scale (0â10). Examiners rated difficulty of examination on a scale of 1â5 (1Â =Â easiest). Results: Visualization with 3Â mm endoscope was superior for the sphenoid ostium (PÂ =Â 0.002), superior turbinate (PÂ =Â 0.007), spheno-ethmoid recess (PÂ =Â 0.006), uncinate process (PÂ =Â 0.002), cribriform area (PÂ =Â 0.007), and Valve of Hasner (PÂ =Â 0.002). Patient discomfort was not significantly different for 3Â mm vs. 4Â mm endoscopes but correlated with the examiners' assessment of difficulty (rÂ =Â 0.73). The examiner rated endoscopy with 4Â mm endoscopes more difficult (PÂ =Â 0.027). Conclusions: The 3Â mm endoscope was superior in visualizing the sphenoid ostium, superior turbinate, spheno-ethmoid recess, uncinate process, cribriform plate, and valve of Hasner. It therefore may be useful in assessment of spheno-ethmoid recess, nasolacrimal duct, and cribriform area pathologies. Overall, patients tolerated nasal endoscopy well. Though patient discomfort was not significantly different between the endoscopes, most discomfort with 3Â mm endoscopes was noted while examining structures difficult to visualize with the 4Â mm endoscope. Patients' discomfort correlated with the examiner's assessment of difficulty. Keywords: Diagnostic, Nasal endoscopy, Pediatric endoscope, 3Â mm endoscope